Design, synthesis and evaluation of 15N- and 13C-labeled molecular probes as hyperpolarized nitric oxide sensors. (15th October 2022) - Park, Hyejin; Eriksson, Shannon; Warren, Warren S.; Wang, Qiu
Graphical abstract: We report the design and development of novel 15 N-and 13 C-labeled NO-sensing probes for hyperpolarized nuclear magnetic resonance (HP-NMR) studies. These probes undergo selective and rapid reaction with NO to generate the AZO-products in situ that can be monitored with distinguishable NMR signals as a read-out. This study also provides direct comparison of the 15 N and 13 C nuclei performances in hyperpolarized reaction-based probes. Abstract: Nitric oxide (NO) is an important signaling molecule involved in a wide range of biological processes. Development of non-invasive, real-time detection of NO is greatly desired yet remains challenging. Here we report the design and development of novel 15 N- and 13 C-labeled NO-sensing probes for hyperpolarized nuclear magnetic resonance (HP-NMR) studies. These probes undergo selective and rapid reaction with NO to generate in situ AZO-products that can be monitored with distinguishable NMR signals as a read-out. This study also allows for a direct comparison of the 15 N and 13 C nuclei performances in hyperpolarized reaction-based probes. The simple and general SABRE-SHEATH hyperpolarization method works on the 15 N- and 13 C-NO-sensing probes. Measured long spin–lattice relaxation ( T 1 ) values, especially for 15 N-NO probes, will allow for real-time reaction-based imaging of NO.